TRANSFORMING HEALTHCARE THROUGH DATA ENGINEERING, PREDICTIVE ANALYTICS, AND AI MODELS - Madhukar Dharavath (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
This article explores how artificial intelligence, predictive analytics, and data engineering have revolutionized contemporary healthcare systems. It investigates how these integrated technologies transform clinical decision-making procedures, operational effectiveness, and patient care delivery. The article examines several topics, such as the fundamentals of data engineering, predictive analytics, AI model architectures, the integration of real-time analytics, and clinical applications. With an emphasis on technical difficulties, data quality control, system integration, and regulatory compliance, it also explores the difficulties and solutions associated with deploying these technologies in healthcare settings. This article illustrates how healthcare organizations use these technologies to move from reactive to proactive care models while enhancing patient outcomes and operational effectiveness through a thorough analysis of current installations and results.